Recurrent venous thrombosis in an adequately anticoagulated patient with pemphigus vulgaris. Issue 1 (December 2016) - Ames, Paul; Graf, Maria; Gentile, Fabrizio
Abstract Background Several autoimmune skin disorders are characterised by an increased risk of thrombosis, with bollous pemphigoid carrying a higher risk than pemphigus vulgaris (PV). We describe the case of a middle aged gentleman who developed recurrent venous thromboembolism despite adequate oral anticoagulation during very active PV that required escalation of treatment to bring the disease under control. Case presentation In May 2014 a 49 year gentleman was admitted for widespread mucocutaneous blistering diagnosed as PV by histology and immunofluorescence. After 6 weeks of treatment with systemic steroids and azathioprine the patient developed pulmonary emboli and started oral anticoagulation with warfarin. In late September, the patient re-presented with a severe flare of PV and a recurrent deep vein thrombosis despite oral anticoagulation within therapeutic range. Warfarin was changed to subcutaneous low molecular heparin in therapeutic dose while treatment for pemphigus was escalated: first azathioprine was switched to mycophenolate mofetil and the steroids dose increased; then due to poor response, intravenous immunoglobulins were given for three courses and finally he received four infusions of Rituximab that induced sustained remission. In April 2015 the dose of mycophenolate was decreased but anticoagulation was continued until the beginning of July 2015 to ensure that decreasing immune suppression did not allow the emergence of another flare with attendant thrombotic risk. Conclusion The case highlights the risk of thrombosis and re-thrombosis in aggressive PV and demands further clinical research in this area to assess the need for thromboprophylaxis in aggressive bollous skin disease.